Global Mental Health and Nutrition: Moving Toward a Convergent Research Agenda - Sparling, Thalia M.; Cheng, Bryan; Deeney, Megan; Santoso, Marianne V.; Pfeiffer, Erin; Emerson, Jillian A.; Amadi, Florence Mariamu; Mitu, Khadija; Corvalan, Camila; Verdeli, Helen; Araya, Ricardo; Kadiyala, Suneetha (Frontiers in Public Health, 2021)
Both malnutrition and poor mental health are leading sources of global mortality, disease and disability. The fields of global food security and nutrition (FSN) and mental health have historically been seen as separate fields of research. Each have undergone substantial transformation, especially from clinical, primary care orientations to wider, sociopolitical approaches to achieve Sustainable Development Goals. In recent years, the trajectories of research on mental health and FSN are further evolving into an intersection of evidence. FSN impacts mental health through various pathways such as food insecurity and nutrients important for neurotransmission. Mental health drives FSN outcomes, for example through loss of motivation and caregiving capacities. They are also linked through a complex and interrelated set of determinants. However, the heterogeneity of the evidence base limits inferences about these important dynamics. Furthermore, interdisciplinary projects and programmes are gaining ground in methodology and impact, but further guidance in integration is much needed. An evidence-driven conceptual framework should inform hypothesis testing and programme implementation. The Agriculture, Nutrition and Health (ANH) Academy Working Group on Mental Health is working towards building this framework. The intersection of mental health and FSN can be an opportunity to invest holistically in advancing thinking in both fields.